Pengaruh Pemberian Metode Resitasi Terhadap Kemampuan Berkomunikasi Siswa Kelas VIII Di MTs Al-Washliyah Selat Besar - Rotuzzahrah Saragih, Umay; Maini Sitepu, Juli (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
Basic concept learning is rooted in educators and the concept of learning is rooted in students. Educators as managers of effective teaching and learning activities must know and master every learning method or model. Teachers can use the question and answer method, assigning assignments (recitation), discussion methods, and there are still many choices of methods that can be used for the success of educational goals. The purpose of this research is to find out how much influence the assignment method (recitation) has on students ' communication skills class VIII. This research is an experimental study, using Pretest-Posttest which was carried out at MTs Al- Washliyah Strait Large, with the research target is class VIII students, then the correlation test analysis technique is used to test the hypothesis. Based on the data obtained from this study, it is known that the relationship between the recitation method on students' communication skills with the Pearson correlation value is 0.078. The basis for making decisions on hypothesis testing in this study is if the Pearson correlation rxy value is between 0.00-0.20, it shows a very low level of correlation, which means that there is an effect of giving the recitation method on students' communication skills. In this case, the Pearson correlation value in the experimental pretest and posttest experimental classes increased by 0.032 so that there was a relationship between giving the recitation method to the communication skills of class VIII students at MTs Al-Washliyah Selat Besar.